PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN POWER POINT TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN 015 RUMBAI JAYA - Alfidah, Nur; Noviana, Eddy; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to determine the effect of using power point learning media on learning outcomes social sciences students grade IV SDN 015 Rumbai Jaya. The subjects of this study were students of grade IV SDN 015 Rumbai Jaya which amounted to 30 students consisting of 10 men anda 20 women. The method used in this research is pre-experiment method with one-group research design pretest-posttest design. In this design, before the prior treatment is given the pretest sample (the initial tes) and the end of the sample study is given a posttest (final test). Data collection techniques in this study researchers using test techniques and documentation techniques. Hypothesis testing is done by using test â€œsimple regressionâ€test. Result of research showed that the test result of student social sciences learning before given treatment in the form of use of power point learning media with average 65,17. Meanwhile learning result after use of power point learning media with average 79,83. The based on hypothesis testing that is by using a simple linear regression test with the help of SPSS 23 got the result of the correlation value between the two data 0,829 which means have a very strong and positive influence between the two variables. Shows thitung value = 7,839 with significance value 0,000 â‰¤ 0,05. Then it can be concluded Ho rejected Ha accepted. Which means that Ha â€œ there is a significant influence of the use of power point learning media to the results of student learning social sciences class IV SDN 015 Rumbai Jayaâ€.Keywords : learning power point, result of learning social science